Effect of antioxidant and optimal antimicrobial mixtures of carvacrol, grape seed extract and chitosan on different spoilage microorganisms and their application as coatings on different food matrices - Rubilar, Javiera F. (2017)
There is growing interest in the use of natural agents with antimicrobial (AM) and antioxidant (AOX) properties. Optimization of the AM capacity for mixtures containing carvacrol, grape seed extract (GSE) and chitosan, against gram-negative (Pseudomonas aeruginosa), gram-positive bacteria (Staphylococcus aureus, Listeria innocua and Enterococcus faecalis) and yeast (Saccharomyces cerevisiae) at 106 cfu mL−1 was studied. To observe the synergistic or antagonistic effect and find optimal combinations between the three agents, a simplex centroid mixture design was run for each microorganism, combining carvacrol (0-300 ppm, X1)X, GSE (0-2000 ppm, X2) and chitosan (0-2% w/v, X3). Results of the response surface analysis showed several synergistic effects for all microorganisms. Combinations of 60 ppm-400 ppm-1.2% w/v (carvacrol-GSE-chitosan; optimal AM combination 1, OAMC-1); 9.6 ppm-684 ppm-1.25% w/v (OAMC-2); 90 ppm-160 ppm-1.24% w/v (OAMC-3) were found to be the optimal mixtures for all microorganisms. Radical scavenging activity (RSA) of the same agents was then compared with a standard AOX (butylated hydroxytoluene; BHT) at different concentrations (25, 50 and 100 ppm; as well as the optimal AM concentrations) by the 1,1-diphenyl-2- picrylhydrazyl (DPPH) method. RSA increased in the following order: chitosan< carvacrol< BHT< GSE and for the OAMC: OAMC-2< OAMC-1< OAMC-3. The best RSA (OAMC-3) was applied as a coating in two different food matrices (strawberries and salmon). For strawberries, P. aeruginosa was more sensitive to the action of OAMC-3 than S. cerevisiae. For salmon, S. aureus was more resistant to the action of OAMC-3 than E. faecalis and L. innocua.